Punctuation errors committed in creative writing by Xitsonga grade 10 learners : the case at Mafemani Circuit, Bohlabela District, Mpumalanga Province, South Africa - Ndlovu, Lamisile (My University, 2024)
The study focused on punctuation errors committed by Xitsonga Grade 10 learners when writing narrative essays in Xitsonga Home language. The study was a case study at Mafemani Circuit, Bohlabela District, Mpumalanga Province, in South Africa. The study aimed to examine the types of punctuation errors that learners commit when writing narrative essays, the goal of which was to find an effective approach be used to suppress the problem. The nature of the study and the type of data needed, motivated the researcher to use a qualitative approach. Therefore, the researcher used the qualitative method to collect and analyse the data for this study. This method gave the researcher a variety of opportunities to collect valuable data which helped her gain an in-depth understanding of the study, and the problem researched. In data collection, the researcher used document analysis to analyse learners’ Xitsonga essays. In addition, the researcher conducted unstructured interviews by asking open-ended questions to Xitsonga Home Language educators to ascertain their experiences and knowledge of the types of punctuation errors learners make when writing narrative essays. The findings revealed that learners commit punctuation errors such as the misuse of capital letters, commas, hyphens, semicolons, question marks, full stops, and exclamation marks. The researcher relied on the findings of both the interviews and document analysis, in conjunction with recent empirical studies, to conclude that learners continue to experience many challenges with regard to punctuation marks when they write in Xitsonga. Therefore, the researcher urged educators to put extra effort in teaching punctuation marks to learners.
Thesis (M. (Language Education) -- University of Limpopo, 2024
Keywords: Punctuation; Errors; Narrative; Case study; Writing; Interview; Punctuation; Tsonga language -- Punctuation; Tsonga language -- Study and teaching; Tsonga essays